Artificial Intelligence and the Future of University Education: A Narrative Review - Adam Swidan; Abdullah Abu Kishk; Islam Ibrahim Aiadi; Ali Swidan (European Scientific Journal, ESJ, 2026)
Artificial intelligence is creating a new era in university education, impacting both teaching and learning, as well as new research and institutional administration. The current study is a narrative review of the existing literature on the application of artificial intelligence in the future of higher education. Studies published from 2018 to 2025 were identified from various academic search engines using keywords pertaining to the concepts of AI, higher education, adaptive learning, and educational technology. Selected literature was critically analyzed to obtain the major trends, opportunities, and challenges for the integration of artificial intelligence in the University. From the review results, it was revealed that AI technologies can be leveraged for personalized learning, increase student engagement, aid in academic research, streamline administrative tasks, and boost AI-driven decision-making within higher education institutions. The study also raises a number of concerns related to the use of artificial intelligence, such as privacy and bias issues with data, academic integrity, digital inequalities, and the positions of educators in AI-supported learning settings. The paper underscores the need for institutional policies and responsible implementation practices, as well as ethical governance in AI utilization in universities to guarantee transparency and accountability. The study concludes that the future of university education is likely to depend on the collaborative interaction between the educator and intelligent technologies that will create more flexible, inclusive and innovative learning environment.